Building a Working Capital Optimization Model for Vendor and Distributor Relationship Management - John Oluwaseun Olajide; Bisayo Oluwatosin Otokiti; Sharon Nwani; Adebanji Samuel Ogunmokun; Bolaji Iyanu Adekunle; Joyce Efekpogua Fiemotongha (International Journal of Scientific Research in Civil Engineering, 2023)
This paper develops a comprehensive working capital optimization model tailored for effective vendor and distributor relationship management. Recognizing the critical interplay between liquidity management and supply chain partnerships, the model integrates key financial variables—including inventory levels, payment terms, order frequency, and credit arrangements—with relational factors such as supplier reliability and distributor payment behavior. Using a multi-objective optimization framework supported by deterministic and stochastic analyses, the model balances minimizing working capital requirements with sustaining healthy business relationships. Empirical validation through a case study and simulations demonstrates significant improvements in cash conversion cycles and working capital efficiency, while sensitivity analysis highlights critical parameters influencing financial outcomes. The findings emphasize the value of a holistic approach that aligns financial optimization with relationship management, offering actionable insights for practitioners and a foundation for future research incorporating real-time analytics and behavioral metrics. This integrated framework advances both theoretical and practical understanding of supply chain finance and partnership dynamics in contemporary business environments.